MYSTICAL CONSCIOUSNESS AS CULMINATION OF BHAKTI IN TAGORE - Kannath, Sheila (Journal of Dharma, 2004)
Mysticism can be defined as an attempt to realize the presence of the living God in the soul and in nature. It is a purely personal, individual and spiritual experience. Traces of mysticism are found in Christianity, Hinduism, Islam and other world religions. Many mystics were poets. Poetry or music is the best way to express the feelings of a devotee or bhakta. When God the Eternal Lover touches the heart of a devotee melodies come forth. This is very much true in the experience of the mystic poet, Rabindranath Tagore. When God, the Master Musician, touches him, "the little flute of a reed," his "little heart loses its limits in joy and gives birth to utterance, ineffable." For Tagore the whole universe is God’s song because the holy stream of God’s music breaks through all stony obstacles and rushes on. The poet ever listens to it in silent amazement. His heart longs to join in God’s song.